Experimental Study on the Transverse Effective Bending Rigidity of Segmental Lining Structures - Yong-feng Tang; Han-cheng Chen; Zhen-wei Ye; Ting-jin Liu; Yu-bing Yang (Advances in Civil Engineering)
The transverse effective rigidity ratio is a key parameter when the uniform rigidity ring model is adopted to design or numerically analyse segmental lining structures commonly used on a shield-driven tunnel. Traditionally, the transverse effective rigidity ratio η is treated as a constant, which can be evaluated through theoretical analysis and model tests. In this study, scale models were designed and tested to investigate the variation of the transverse effective rigidity ratio in the segmental linings’ flattening deformation process. The test results suggested that in the elastic stage, the transverse effective rigidity ratio fluctuated between 0.667 and 0.734 for the stagger-jointed rings and fluctuated between 0.503 and 0.642 for the straight-jointed rings. When segmental linings were squashed and started to crack at the circumferential joints, the transverse effective rigidity ratio decreases sharply. Then, a regression equation was obtained to fit the variation trend of η with the increase of horizontal convergence to the outer-diameter ratio (ΔD/Dout). Finally, in a case study, the regression equation was adapted to determine the value of η of an operated shield tunnel which was once surcharged accidentally and deformed severely so as to numerically predict the prospective deformation induced by the upcoming adjacent excavation. Numerical results indicated that as the value of η decreases, the horizontal convergences of shield tunnel induced by adjacent excavation increase significantly and even more than doubled in the case study. Comparatively, through taking account of the operating tunnels’ exiting transverse deformation, the predicted deformation tends to be unfavourable.